A study on the association between HSV-2 and HIV serostatus in HIV seropositive and HIV seronegative individuals - Naga, Ravichitra Katta; Oruganti, Satyanarayana (International Journal of Research in Medical Sciences, 2017)
Background: HSV-2 is a common cause of genital ulcer disease worldwide and has become a prominent public health issue over recent years. The major public health importance of HSV-2 relates to its potential role in facilitating HIV transmission. This study was done to know the association of HSV-2 and HIV, to compare the seropositivity of HSV-2 in HIV seropositive and HIV seronegative individuals and also to study the influence of certain factors on HSV-2 infection. Methods: Blood samples collected from 132 HIV seropositive individuals and 50 HIV seronegative blood donors were screened for HSV-2 type specific IgG antibodies by ELISA. Results: 84 samples of the test group tested positive for HSV-2 (63.63%), which is significantly higher compared to 3 (6%) positives of the control group. HSV-2 seropositivity was significantly higher in individuals with multiple sexual partners, illiterates, daily wage workers. Conclusions: High seropositivity of HSV-2 in HIV seropositive individuals demonstrates the need for regular screening of HSV-2 in HIV seropositive individuals. It also clearly shows that education and occupation will influence the prevalence of HIV and HSV-2.